2010
DOI: 10.1128/aem.00928-10
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of Sortase A in Lactococcus lactis

Abstract: Lactococcus lactis IL1403 harbors a putative sortase A (SrtA) and 11 putative sortase substrates that carry the canonical LPXTG signature of such substrates. We report here on the functionality of SrtA to anchor five LPXTG substrates to the cell wall, thus suggesting that SrtA is the housekeeping sortase in L. lactis IL1403.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 46 publications
1
48
1
Order By: Relevance
“…Both mutants contain in-frame deletions of approximately 90 % of the sortase gene. Due to the deficiency of SrtA, these strains are also expected to lack the surface display of predicted SDPs (Dieye et al, 2010;Remus et al, 2013). When both DsrtA mutants were examined for their growth characteristics in culture medium (MRS) and survival in SGJ and SIJ, neither L. acidophilus NCK2232 nor L. gasseri NCK2256 showed growth impairment or increased LGAS_1725 1993 2 *The presence of a signal peptide was determined using InterProScan (http://www.ebi.ac.uk/Tools/pfa/iprscan/).…”
Section: Construction Of Sortase-deficient Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both mutants contain in-frame deletions of approximately 90 % of the sortase gene. Due to the deficiency of SrtA, these strains are also expected to lack the surface display of predicted SDPs (Dieye et al, 2010;Remus et al, 2013). When both DsrtA mutants were examined for their growth characteristics in culture medium (MRS) and survival in SGJ and SIJ, neither L. acidophilus NCK2232 nor L. gasseri NCK2256 showed growth impairment or increased LGAS_1725 1993 2 *The presence of a signal peptide was determined using InterProScan (http://www.ebi.ac.uk/Tools/pfa/iprscan/).…”
Section: Construction Of Sortase-deficient Mutantsmentioning
confidence: 99%
“…Similarly, SDPs play a role in the virulence of several other Gram-positive pathogenic species such as Listeria monocytogenes (Bierne et al, 2002) and Streptococcus pneumoniae (Paterson & Mitchell, 2006). Meanwhile, the role of SrtA has only recently been studied in species of commensal and probiotic microbes, including Lactobacillus casei BL23 (Muñoz-Provencio et al, 2012), Lactococcus lactis IL1403 (Dieye et al, 2010), Lactobacillus plantarum WCFS1 (Remus et al, 2013) and Lactobacillus salivarius UCC118 (O'Callaghan et al, 2012;van Pijkeren et al, 2006). These studies demonstrated that SrtA and SDPs play pivotal roles in the adhesion to intestinal epithelial cells (IECs), immune modulation of DCs, as well as the expression of mucin genes in Caco-2 IECs.…”
Section: Introductionmentioning
confidence: 99%
“…The transpeptidase sortase A (SrtA) covalently anchors proteins containing an LPXTG motif to the cell wall of a range of Gram-positive bacteria (5)(6)(7)(8)(9). S. epidermidis RP62A expresses 11 proteins containing an LPXTG motif (10).…”
mentioning
confidence: 99%
“…This has been reported for sortase mutants of different classes in many Gram-positive microorganisms including LAB. That is the case for the different mutants of L. casei BL23 obtained in this study and also for the srtA deletion mutant in the model LAB L. lactis (Dieye, et al, 2010). Only in the case of Bacillus anthracis class B sortase and under iron-limiting conditions significant growth defects have been detected (Maresso, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to recent results obtained in L. lactis, where a srtA mutation completely abolished the anchoring to the cell wall of all the sortase substrates tested. Therefore, as reported for many other Grampositive bacteria, srtA is the single gene responsible for the general sortase activity in L. lactis (Dieye, et al, 2010) Also, Dieye and coworkers used two-dimensional gel electrophoresis of surface proteins to search for proteins absent in the L. lactis srtA mutant, and they identified several sortase substrates (Dieye, et al, 2010). However, and in agreement with the results of surface anchoring, our efforts to detect the absence/reduction of surface proteins in the BL23 srtA1/srtA2 mutant by this technique were not successful (data not shown).…”
Section: Discussionmentioning
confidence: 99%